Managing Eating Disorders on a General Pediatrics Unit: A Centralized Video Monitoring Pilot. Issue 6 (8th April 2019) - Shadman, Kristin A; Coller, Ryan J; Smith, Windy; Kelly, Michelle M; Cody, Paula; Taft, William; Bodine, Laura; Sklansky, Daniel J
Abstract : Adolescents with severe eating disorders require hospitalization for medical stabilization. Supervision best practices for these patients are not established. This study sought to evaluate the cost and feasibility of centralized video monitoring (CVM) supervision on a general pediatric unit of an academic quaternary care center. This was a retrospective cohort study of nursing assistant (NA) versus CVM supervision for girls 12‐18 years old admitted for medical stabilization of an eating disorder between September 2013 and March 2017. There were 37 consecutive admissions (NA = 23 and CVM = 14). NA median supervision cost was more expensive than CVM (4, 104/admission vs 1, 166/admission, P < .001). Length of stay and days to weight gain were not statistically different. There were no occurances of family refusal of CVM, conversion from CVM to NA, technological failure, or unplanned discontinuation. Video monitoring was feasible and associated with lower supervision costs than one‐to‐one NA supervision. Larger samples in multiple centers are needed to confirm the safety, acceptability, and efficacy of CVM.